Upaya Penyelesaian Non Litigasi Terhadap Kumpul Kebo Di Desa Naiola Kecamatan Bikomi Selatan Kabupaten Timor Tengah Utara - Antonius Padua Naicea; Rudepel Petrus Leo; Deddy R. Ch. Manafe (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The widespread social phenomenon of "cohabitation" often occurs because there is a legal space that allows this practice to develop. The local government has made various efforts to minimize this phenomenon, but without adequate legal force, these efforts often do not have the desired deterrent effect. However, the local customary law approach can provide a legal basis that is stronger and relevant to local values, so that the community can be more responsive to the regulations implemented. Thus, it is hoped that through this approach, the phenomenon of "cohabitation" can be minimized and overcome more effectively. This research aims to complete a non-litigation resolution of cohabitation in Naiola Village before Law Number 1 of 2023. The research method used in this research is empirical legal research, namely legal research that obtains data from primary data or data obtained directly from the community. Non-litigation resolution of cohabitation often relies on customary law-based approaches and customary deliberation that utilize local values and traditional mechanisms to achieve a harmonious resolution that is accepted by the local community. Thus, this research provides a clear picture of the importance of non-litigation resolution of cohabitation by utilizing customary law and traditional deliberation approaches to achieve a harmonious solution that is accepted by the local community.